Neuroanatomy for the Neuroscientist - Jacobson, Stanley (Springer International Publishing, 2018)
The purpose of this textbook is to enable a Neuroscientist to discuss the structure and functions of the brain at a level appropriate for students at many levels of study including undergraduate, graduate, dental or medical school level. It is truer in neurology than in any other system of medicine that a firm knowledge of basic science material, that is, the anatomy, physiology and pathology of the nervous system, enables one to readily arrive at the diagnosis of where the disease process is located and to apply their knowledge at solving problems in clinical situations. The authors have a long experience in teaching neuroscience courses at the first or second year level to medical and dental students and to residents in which clinical information and clinical problem solving are integral to the course.